2005
DOI: 10.1016/j.femsec.2005.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Non-specific biodegradation of the organophosphorus pesticides, cadusafos and ethoprophos, by two bacterial isolates

Abstract: An enrichment culture technique was used for the isolation of microorganisms responsible for the enhanced biodegradation of the nematicide cadusafos in soils from a potato monoculture area in Northern Greece. Mineral salts medium supplemented with nitrogen (MSMN), where cadusafos (10 mg l(-1)) was the sole carbon source, and soil extract medium (SEM) were used for the isolation of cadusafos-degrading bacteria. Two pure bacterial cultures, named CadI and CadII, were isolated and subsequently characterized by se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(33 citation statements)
references
References 36 publications
4
28
1
Order By: Relevance
“…Our results are in agreement with previous finding reported by Kopytko et al (2002), Karpouzas et al (2005), Belal et al (2008), Derbalah and Belal (2008) and Megadi et al (2010). It was found that enrichment culture technique led to the isolation of two bacterial strains, which were able to degrade different pesticides rapidly in liquid cultures.…”
Section: Isolation Of the Pendimethalin-dissipation Isolatessupporting
confidence: 94%
“…Our results are in agreement with previous finding reported by Kopytko et al (2002), Karpouzas et al (2005), Belal et al (2008), Derbalah and Belal (2008) and Megadi et al (2010). It was found that enrichment culture technique led to the isolation of two bacterial strains, which were able to degrade different pesticides rapidly in liquid cultures.…”
Section: Isolation Of the Pendimethalin-dissipation Isolatessupporting
confidence: 94%
“…It showed the highest sequence similarities with P. resinovorans ATCC14235. These results are in agreement with previous finding reported by (Kopytko et al, 2002;Karpouzas et al, 2005;Belal et al, 2008;Derbalah and Belal, 2008;Megadi et al, 2010;Belal and El-Nady, 2013). It was found that enrichment culture technique led to the isolation of two bacterial strains, which were able to degrade different pesticides rapidly in liquid cultures.…”
Section: Isolation Of the Pendimethalin-degrading Bacteriasupporting
confidence: 93%
“…Fenitrothion significantly decreased the microbial respiration, during whole experimental period, in soils treated with 10 and 200 mg/kg soil of insecticide, with the exception of the last day of experiment. It has been found that fenitrothion, like other organophosphorus pesticides, may be degraded by many soil microorganisms resulting in the increase of microbial biomass and their respiration rate (Karpouzas et al 2005;Hong et al 2007), but this phenomenon was not observed in our study. The negativ effect of used insecticide may be associated with the high toxicity of intermediate metabolites that are the products of fenitrothion biodegradation (Matsushita et al 2003).…”
Section: Microbial Soil Respirationcontrasting
confidence: 79%